2018
DOI: 10.1186/s12906-018-2261-2
|View full text |Cite
|
Sign up to set email alerts
|

Prescription patterns of traditional Chinese medicine amongst Taiwanese children: a population-based cohort study

Abstract: BackgroundTraditional Chinese medicine (TCM) has been used by Chinese patients and in many other countries worldwide. However, epidemiological reports and prescription patterns on children are few.MethodsA cohort of 178,617 children aged 18 and under from one million randomly sampled cases of the National Health Insurance Research Database was analyzed for TCM prescription patterns. SAS 9.1 was applied and descriptive medicine utilization patterns were presented.ResultsThe cohort included 112,889 children trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…An excellent prescription was made on the foundation of precise and flexible theory, method, formula, and herbs, and exploring the standardization of TCM clinical prescriptions was of great significance to improve the prescription quality and enhance doctors' academic level, as well as promote rational drug use and guarantee the medical security [ 21 ]. Prescription reviews usually refer to the analysis and evaluation of the rationality of prescriptions issued by doctors, and to promote their effective application in the TCM preparation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…An excellent prescription was made on the foundation of precise and flexible theory, method, formula, and herbs, and exploring the standardization of TCM clinical prescriptions was of great significance to improve the prescription quality and enhance doctors' academic level, as well as promote rational drug use and guarantee the medical security [ 21 ]. Prescription reviews usually refer to the analysis and evaluation of the rationality of prescriptions issued by doctors, and to promote their effective application in the TCM preparation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although Western medicine is the mainstream in Taiwan, about 30% of patients have used TCM to treat problems and diseases of the major human organ systems recognized by Western medicine 17 . Several studies have reported on TCM uses among patients with different diseases, based on analysis of the NHIRD 18‐21 …”
Section: Discussionmentioning
confidence: 99%
“…This de-identified database contained registration files and original claim data, constructed in many data subset for research purposes [5]. Many published studies used this database [6][7][8][9][10][11][12]. A representative subset of two million people was randomly sampled from the 24 million beneficiaries of the Taiwan NHI between 2006 and 2013.…”
Section: Data Sources and Study Populationmentioning
confidence: 99%